Interaction of green tea catechins with renal organic cation transporter 2 - Chaliya Jaiyen (2018)
© 2015 Taylor & Francis. 1. Green tea extract (GTE) and EGCG have previously shown to increase the uptake of MPP+into Caco-2 cells. However, whether GTE and its derivatives interact with renal basolateral organic cation transporter 2 (Oct2) which plays a crucial role for cationic clearance remains unknown. Thus, this study assessed the potential of drug-green tea (GT) catechins and its derivatives interactions with rat Oct2 using renal cortical slices and S2 stably expressing rat Oct2 (S2rOct2).2. Both GTE and ECG inhibited MPP+uptake in renal slices in a concentration-dependent manner (IC50 = 2.71 ± 0.360 mg/ml and 0.87 ± 0.151 mM), and this inhibitory effect was reversible. Inhibition of [3H]MPP+transport in S2rOct2 by either GTE or ECG (IC50 = 1.90 ± 0.087 mg/ml and 1.67 ± 0.088 mM) was also observed.3. The weak and reversible interactions of GTE and ECG with rOct2 indicate that consumption of GT beverages could not interfere with cationic drugs secreted via renal OCT2 in humans. However, the rise of therapeutic use of GTE and ECG might have to take into account the significant possibility of adverse drug-green tea catechins interactions which could alter renal organic cation drug clearance.